Design of Bi-Tortuous, Anisotropic Graphite Anodes for Fast Ion-Transport in Li-Ion Batteries. Issue 8 (6th May 2015) - Nemani, V. Pavan; Harris, Stephen J.; Smith, Kyle C.
Abstract : Thick Li-ion battery electrodes with high ion transport rates could enable batteries that cost less and that have higher gravimetric and volumetric energy density, because they require fewer inactive cell-components. Finding ways to increase ion transport rates in thick electrodes would be especially valuable for electrodes made with graphite platelets, which have been shown to have tortuosities in the thru-plane direction about 3 times higher than in the in-plane direction. Here, we predict that bi-tortuous electrode structures (containing electrolyte-filled macro-pores embedded in micro-porous graphite) can enhance ion transport and can achieve double the discharge capacity compared to an unstructured electrode at the same average porosity. We introduce a new two-dimensional version of porous-electrode theory with anisotropic ion transport to investigate these effects and to interpret the mechanisms by which performance enhancements arise. From this analysis we determine criteria for the design of bi-tortuous graphite anodes, including the particular volume fraction of macro-pores that maximizes discharge capacity (approximately 20 vol.%) and a threshold spacing interval (half the electrode's thickness) below which only marginal enhancement in discharge capacity is obtained. We also report the sensitivity of performance with respect to cycling rate, electrode thickness, and average porosity/electroactive-material loading.